Practice of the Social Forestry Development Program as a Forest Conservation Strategy in Yehembang Kangin Village - Centauri, Farkha Alfa; Seva, Tahsa Ayu; Dinasti, Galang Alhaya; Pamungkas, Hendra Bagus (Global Writing Academica Researching and Publishing, 2024)
The rate of development and economic growth of a region is inextricably linked to various activities that pose risks to environmental degradation, including forest destruction. This is concretely evidenced by the increasing cases of forest encroachment in the Jembrana Regency. Such encroachment is triggered by activities like “ngawen” and illegal logging, leading to environmental damage and loss of biodiversity. In this context, PT Pertamina Patra Niaga Aviation Fuel Terminal (AFT) Ngurah Rai plays a role in supporting the development of social forestry programs in Yehembang Kangin Village, Mendoyo District, Jembrana Regency, Bali Province, to raise community awareness on the importance of forest conservation and empower the community members of the Banu Giri Lestari Forest Farmer Group sustainably. This research employed a descriptive qualitative approach supported by purposive sampling data collection techniques. The results of this study indicate that the social forestry development program in Yehembang Kangin Village has brought positive changes in the group’s behavior towards forest conservation. This program has produced local heroes and their successors, who are expected to become agents of change in the wise and responsible management of forests. Additionally, the group has initiated independent cultivation of timber and fruit trees by practicing the “tanem tuwuh” (plant to grow) pattern to support ecosystem sustainability and increase the diversity of flora and fauna within the forest.